Measuring the impact of a social programme on healthcare: a 10-year retrospective cohort study in Trieste, Italy - Luigi Castriotta; Manuela Giangreco; Maria Grazia Cogliati-Dezza; Marco Spanò; Enrico Atrigna; Claudia Ehrenfreund; Valentina Rosolen; Flavio Paoletti; Fabio Barbone (BMJ Open)
Objectives Poor social conditions are strong determinants of poor health but positive health and healthcare changes caused by social interventions are difficult to demonstrate. In 2006, in Trieste (Italy), a social intervention known as ‘Habitat Microaree’ (HM) project was implemented in eight deprived neighbourhoods. In 2016, an observational study was launched to assess the impact of the HM project on healthcare.Design Retrospective cohort study.Setting The eight geographically defined neighbourhoods of Trieste involved in the 2006 HM project, accounting for a total of 11 380 residents.Participants Participants were all residents in the intervention areas. By means of a propensity score based on deprivation index, age, sex, Charlson index and drug utilisation, a non-participating, comparison group was defined.Intervention The community-based intervention consisted of facilitating access to social services and outpatient healthcare facilities, coordinating intersectoral public services and specifically planning hospital discharge. These services were not provided in other areas of the city.Outcome measures Hospital admissions and emergency department access.Results We followed 16 256 subjects between 2008 and 2015. Living in microareas was associated with an HR for first hospital admission, for all causes, of 0.95 (95% CI 0.91 to 0.99); while the HR for urgent admissions in females was 0.92 (95% CI 0.85 to 1.00). The HR for psychiatric disorders, in females, was 0.39 (95%CI 0.18 to 0.82); in particular, the HR for psychosis was 0.15 (95% CI 0.05 to 0.51). The HR for acute respiratory diseases in females was 0.44 (95% CI 0.21 to 0.95). In males, the HR for genitourinary diseases and heart diseases were 0.65 (95% CI 0.42 to 1.01) and 0.72 (95% CI 0.54 to 0.97), respectively. Concerning urgent multiple admissions, the OR for fractures in females was 0.75 (95% CI 0.58 to 0.97).Conclusion In the study period, the effects on healthcare appear evident, especially in females.